Therapeutic and analytical applications of arsenic binding to proteins. Issue 1 (30th October 2014) - Chen, Beibei; Liu, Qingqing; Popowich, Aleksandra; Shen, Shengwen; Yan, Xiaowen; Zhang, Qi; Li, Xing-Fang; Weinfeld, Michael; Cullen, William R.; Le, X. Chris
Abstract : Knowledge of arsenic binding to proteins advances the development of bioanalytical techniques and therapeutic drugs. Abstract : Arsenic binding to proteins plays a pivotal role in the health effects of arsenic. Further knowledge of arsenic binding to proteins will advance the development of bioanalytical techniques and therapeutic drugs. This review summarizes recent work on arsenic-based drugs, imaging of cellular events, capture and purification of arsenic-binding proteins, and biosensing of arsenic. Binding of arsenic to the promyelocytic leukemia fusion oncoprotein (PML-RARα) is a plausible mode of action leading to the successful treatment of acute promyelocytic leukemia (APL). Identification of other oncoproteins critical to other cancers and the development of various arsenicals and targeted delivery systems are promising approaches to the treatment of other types of cancers. Techniques for capture, purification, and identification of arsenic-binding proteins make use of specific binding between trivalent arsenicals and the thiols in proteins. Biarsenical probes, such as FlAsH-EDT2 and ReAsH-EDT2, coupled with tetracysteine tags that are genetically incorporated into the target proteins, are used for site-specific fluorescence labelling and imaging of the target proteins in living cells. These allow protein dynamics and protein–protein interactions to be studied. Arsenic affinity chromatography is useful for purification of thiol-containing proteins, and its combination with mass spectrometry provides a targeted proteomic approach for studying the interactions between arsenicals and proteins in cells. Arsenic biosensors evolved from the knowledge of arsenic resistance and arsenic binding to proteins in bacteria, and have now been developed into analytical techniques that are suitable for the detection of arsenic in the field. Examples in the four areas, arsenic-based drugs, imaging of cellular events, purification of specific proteins, and arsenic biosensors, demonstrate important therapeutic and analytical applications of arsenic protein binding.